Calibration of a Harmonic State Estimation to Assess the Connection of Solar PV Systems in Distribution Networks - Bermeo, Alex Daniel Lozado; Bermeo, Diego Pául Guachichullca; Asanza, Sergio Patricio Zambrano [UNESP]; Matute, Geovanny Armando Matute; Fernández, Juan Sanango; Baquero, John Fredy Franco [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2023)
This paper presents an analysis of the distribution system harmonic behavior when a photovoltaic (PV) system is connected at the low-voltage network. Through harmonic power flow simulations in the Open Distribution System Simulator (OpenDSS), harmonic impact at the point common coupling is studied. To reduce the harmonic analysis, simulations are carried out using a simplified equivalent for utility and customer. In order to model a more realistic distribution system, it is necessary to calibrate the harmonic sources before connecting the PV system. The harmonic state estimation method implemented in combination with the simulator is used to calibrate the utility harmonic voltage sources. After calibration, the harmonic levels at medium-voltage are verified. Results for a case study using quality measurements performed by Ecuadorian CENTROSUR electric utility show that the simulated harmonic levels are similar to those measured. It also shows that a PV system does not produce power quality problems.
Keywords: Harmonic analysis; harmonic current; harmonic state estimation; harmonic voltage; PV system